2022
DOI: 10.1038/s41467-022-33572-7
|View full text |Cite
|
Sign up to set email alerts
|

RNA export through the nuclear pore complex is directional

Abstract: The changes occurring in mRNA organization during nucleo-cytoplasmic transport and export, are not well understood. Moreover, directionality of mRNA passage through the nuclear pore complex (NPC) has not been examined within individual NPCs. Here we find that an mRNP is compact during nucleoplasmic travels compared to a more open structure after transcription and at the nuclear periphery. Compaction levels of nuclear transcripts can be modulated by varying levels of SR proteins and by changing genome organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Notably, in cytoplasmic extract, the nanobody could bind GFP-EIF4A3 also in the heavy gradient fractions (Extended Data Fig. 10d), in agreement with a lower degree of compaction in cytoplasmic compared to nuclear mRNPs and the absence of TREX in the cytoplasm 15,16 . Further, we observed that all endogenously tagged GFP-THOC5 or lentiviral overexpressed THOC1-GFP could be immunoprecipitated using anti-GFP nanobody beads from the respective nuclear extracts (Extended Data Fig.…”
Section: Mrnps Form Compact Globulessupporting
confidence: 63%
“…Notably, in cytoplasmic extract, the nanobody could bind GFP-EIF4A3 also in the heavy gradient fractions (Extended Data Fig. 10d), in agreement with a lower degree of compaction in cytoplasmic compared to nuclear mRNPs and the absence of TREX in the cytoplasm 15,16 . Further, we observed that all endogenously tagged GFP-THOC5 or lentiviral overexpressed THOC1-GFP could be immunoprecipitated using anti-GFP nanobody beads from the respective nuclear extracts (Extended Data Fig.…”
Section: Mrnps Form Compact Globulessupporting
confidence: 63%
“…Our dissipative particle dynamics (DPD) model has qualitatively recapitulated the experimental results from living cells that mechanomemory persists in the chromatin, and nucleoplasm diffusivity for tens of minutes after stress cessation and this memory is regulated by the NPCs. Recent reports show that the size of and the transport via the NPCs that is tethered to the cytoskeleton is regulated by the tension in the nuclear envelope ( 21 , 27 ), and transport of RNA via NPCs is unidirectional ( 28 ). Our current finding that the mechanomemory of chromatin diffusivity and nucleoplasm protein diffusivity extends the current understanding of the role of the NPCs and highlights the importance of the molecular exchange between the nucleus and the cytoplasm in regulating external force-induced nuclear activities and functions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although this process is ATP dependent in opisthokonts [67], the lack of many ATPases in the nuclear pore complex of trypanosomatids suggests that mRNA nuclear export is GTP driven in these organisms [68,69]. Assuming that the amount of HEBs (high-energy bonds) consumed by T. brucei for RNA nuclear export is the same as that consumed by yeast (i.e., 2 ATP molecules per transcript) [70,71] we can estimate a cost for the export of the total number of rRNAs (those for maintenance and those for duplication) minus the SL-RNAs, which remain in the nucleus. The total HEB equivalent to ATP used for this process is 3.1 x 10 5 for rRNAs, 4.0 x 10 3 for VSG mRNAs and 7.6 x 10 4 for all other mRNAs.…”
Section: Plos Pathogensmentioning
confidence: 99%